Health System Resilience as the Basis for Explanation Versus Evaluation; Comment on “The COVID-19 System Shock Framework: Capturing Health System Innovation During the COVID-19 Pandemic” - Stephanie Topp (International Journal of Health Policy and Management, 2023)
The onset and impacts of COVID-19 have prompted attention to national health system preparedness for, and capacity to adapt in response to, public health emergencies and other shocks. This preparedness and adaptive capacity are often framed as ‘health system resilience’ a concept previously associated more with assessments of health systems in conflict-affected and fragile states. Yet health system resilience remains a slippery concept, defined and applied in multiple ways. Reflecting on the Hodgins and colleagues’ study “the COVID-19 system shock framework: capturing health system innovation during the COVID-19 pandemic,” this article restates the limitations of health systems resilience as a concept capable of anchoring evaluative assessments of health system performance but stresses its value in the context of explanatory research investigating how and why health systems adapt, with due attention to the power of actors’ whose choices inform the nature and direction of change.